China Belt and Road Initiative: Give-and-Take of Infrastructure Development in the North Africa Subregion - Dzekashu, William G.; Anyu, Julius N. (World Journal of Business and Management, 2024)
It is not a secret that Africa is richly endowed with raw materials, which has raised the stakes for foreign interests. The amplification of these riches has created a sense of urgency in developed nations to enter partnerships to have access to the resources. North Africa, though more advance than its sub-Saharan neighbors falls in the essential corridor of the Belt and Roads Initiative (BRI); and thus, requires infrastructure improvement to meet the overall BRI agenda. This yearning for infrastructure development in Africa has generally been met by China’s search for natural resources. The BRI is that infrastructure investment platform that allows for connectivity between member nations. This semi-systematic literature review identifies and appraises relevant research and collects and analyzes data about the impact of BRI on development in this subregion. Even though the BRI has shown some evidence of constructive growth in infrastructure connectivity, the opaque nature of the engagements has been the subject of harsh criticism; with some critics describing China’s motive as an attempt to recolonize Africa. Chinese partnerships in Africa have resulted in major investments and credit flows providing the much-needed resources to the BRI member countries to implement the very much needed development schemes, despite the main challenge that remains—sustenance of these extensive projects. The most significant implication of the BRI has been the concern about a possible conflict between China and the US. A key to averting open conflict between China and the US is through an alliance and coordinated response by Europe and the US.